Analisis Indikator Makro Terhadap Kurs Di Indonesia - Rifki Khoirudin (Tirtayasa Ekonomika, 2022)
This study aims to analyze macro indicators against the rupiah exchange rate against the United States dollar using the Vector Error Correction Model (VECM) in the period January 2010 to December 2020. In the modeling, several macroeconomic variables are used against the rupiah exchange rate against the United States dollar, namely export, import, money supply, and inflation. This type of research uses a quantitative approach. The results of this study indicate that in the long and short term, the export variable has a significant negative effect on the rupiah exchange rate against the US dollar. In the long and short term, the import variable has a significant positive effect on the rupiah exchange rate against the United States dollar. And in the long and short term, the money supply and inflation variables has no significant effect on the rupiah exchange rate against the United States dollar.